Pre- and postnatal maternal depressive symptoms associated with local connectivity of the left amygdala in 5-year-olds - Vartiainen, Elena; Copeland, Anni; Pulli, Elmo P.; Kumpulainen, Venla; Silver, Eero; Rajasilta, Olli; Jolly, Ashmeet; Luotonen, Silja; Audah, Hilyatushalihah K.; Hashempour, Niloofar; Bano, Wajiha; Suuronen, Ilkka; et al. (Cambridge University Press, 2026)
Background. Maternal depressive symptoms can influence brain development in offspring, prenatally through intrauterine programming, and postnatally through caregiving related mother–child interaction.
Methods. The participants were 5-year-old mother–child dyads from the FinnBrain Birth Cohort Study (N = 68; 28 boys, 40 girls). Maternal depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale (EPDS) at gestational week 24, 3 months, 6 months, and 12 months postnatal. Children’s brain imaging data were acquired with task-free functional magnetic resonance imaging (fMRI) at the age of 5 years in 7-min scans while watching the Inscapes movie. The derived brain metrics included whole-brain regional homogeneity (ReHo) and seed-based connectivity maps of the bilateral amygdalae.
Results. We found that maternal depressive symptoms were positively associated with ReHo values of the left amygdala. The association was highly localized and strongest with the maternal depressive symptoms at 3 months postnatal. Seed-based connectivity analysis did not reveal associations between distal connectivity of the left amygdala region and maternal depressive symptoms.
Conclusions. These results suggest that maternal depressive symptoms soon after birth may influence offspring’s neurodevelopment in the local functional coherence in the left amygdala. They underline the potential relevance of postnatal maternal distress exposure on neurodevelopment that has received much less attention than prenatal exposures. These results offer a possible thus far understudied pathway of intergenerational effects of perinatal depression that should be further explored in future studies.